Causes of regionalism. How ASEAN-China FTA fits the (new) wave of regionalism - Miková, Ivana
Koncepcia regionalizmu. Tri vlny regionalizmu. ASEAN-Čína v kontexte v kontexte regionalizmu východnej Ázie.